O os the centre of circle ⭕ then prove that aoc = afc+ aec
Answers
Answer:
Given:- In the given fig., O is the centre of circle.
To prove:- ∠AOC=∠AFC+∠AEC
Proof:- In △BEC, Exterior angle at B,
∴∠ABC=∠AEC+∠BCD.....(1)(Exterior angle theorem)
2∠ABC=2∠AEC+∠BCD
∵2∠ABC=∠AOC(Angle subtended on circle is double the angle subtended at centre on same arc)
∴∠AOC=∠AEC+∠BCD+∠AEC+∠BCD
∠AOC=∠AEC+∠BCD+∠ABC(From (1))
∵∠ABC=∠ADC(∵Angle subtends on same arc are equal)
∴∠AOC=∠AEC+∠BCD+∠ADC.....(2)
Now, in △FDC
Exterior angle at F.
∴∠AFC=∠BCD+∠ADC.....(3)
Now, from equation (2)&(3), we have
∠AOC=∠AEC+∠AFC
Step-by-step explanation:
Given: In the given figure O is the centre of the circle.
To Prove: \angle AOC=\angle AFC+\angle AEC∠AOC=∠AFC+∠AEC
Proof: In ΔBEC using exterior angle theorem.
Exterior angle theorem property: Sum of two interior angle of triangle is equal to opposite exterior angle. So, we get
\angle ABC=\angle AEC+\angle BCD∠ABC=∠AEC+∠BCD
Double the above equation both sides
2\angle ABC=2\angle AEC+2\angle BCD2∠ABC=2∠AEC+2∠BCD
Angle subtended on circle is half angle subtended at centre.
2\angle ABC=\angle AOC2∠ABC=∠AOC
\angle AOC=\angle AEC+\angle BCD+\angle AEC+\angle BCD∠AOC=∠AEC+∠BCD+∠AEC+∠BCD
\angle AOC=\angle AEC+\angle BCD+\angle ABC∠AOC=∠AEC+∠BCD+∠ABC
\text{But } \angle ABC=\angle ADCBut ∠ABC=∠ADC (∴ Angles subtended on same arc are equal)
\angle AOC=\angle AEC+\angle BCD+\angle ADC∠AOC=∠AEC+∠BCD+∠ADC
In ΔFDC using exterior angle theorem.
\angle AFC=\angle BCD+\angle ADC∠AFC=∠BCD+∠ADC
\therefore \angle AOC=\angle AEC+\angle AFC∴∠AOC=∠AEC+∠AFC
\text{Hence proved, } \angle AOC=\angle AFC+\angle AECHence proved, ∠AOC=∠AFC+∠AEC